Hyper academia. Issue 2 (4th July 2018) - Munar, Ana María
Abstract : Purpose: What ought we morally to do in a tourism academia dominated by metrics, quantification and digital codification? The purpose of this paper is to address this question by presenting the idea of "hyper academia" and exploring ethical perspectives and values related to hyper-digital cultures. Design/methodology/approach: Drawing inspiration from classical and post-disciplinary traditions, the topic is exposed in a creative and multi-layered way using conceptual, philosophical and artistic tools. It is structured in four sections: An introductory essay on gratitude, a philosophical thought experiment, a literary short story and a manifesto. Findings: Gratitude referencing is a method of personalizing the attribution of influence in scholarship and restoring the importance of depth and slowness over speed, novelty and quantity. The thought experiment allows us to see how we make value judgements on academic work under different scenarios. The dystopian short story shows the radical power that such a genre has to create emotional engagement whilst activating our critical reflexivity. Finally, the manifesto answers the question of what we morally "ought to do" by inviting scholars to engage with five duties. Originality/value: This paper looks beyond previous descriptive studies of academic rankings and metrics, inviting tourism scholars to reflect on the values and moral justifications behind our evaluation cultures.